2016
DOI: 10.1186/s12889-016-2969-1
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and environmental characteristics of smokers with a mental illness, and associations with quitting behaviour and motivation; a cross sectional study

Abstract: BackgroundPersons with a mental illness are less likely to be successful in attempts to quit smoking. A number of smoking and environmental characteristics have been shown to be related to quitting behaviour and motivation of smokers generally, however have been less studied among smokers with a mental illness. This study aimed to report the prevalence of smoking characteristics and a variety of physical and social environmental characteristics of smokers with a mental illness, and explore their association wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 61 publications
(83 reference statements)
2
17
0
Order By: Relevance
“…Studies of cigarette smokers attempting to quit that are screened for mental health disorders show that around half of these smokers have at least one mental disorder, and two-thirds of those have more than one disorder [55]. Having multiple comorbid disorders increases the probability of smoking relapse and is associated to heavier smoking and a reduced likelihood of quitting smoking [56]. Furthermore, studies of adults with mental illnesses that estimate the prevalence of smoking show that smoking prevalence increases with the number of comorbid mental illnesses and that smokers with a mental disorder have lower success in quitting than smokers without mental illnesses [57] although there is solid evidence for the effectiveness of smoking cessation interventions for people even with severe mental disorders [58].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of cigarette smokers attempting to quit that are screened for mental health disorders show that around half of these smokers have at least one mental disorder, and two-thirds of those have more than one disorder [55]. Having multiple comorbid disorders increases the probability of smoking relapse and is associated to heavier smoking and a reduced likelihood of quitting smoking [56]. Furthermore, studies of adults with mental illnesses that estimate the prevalence of smoking show that smoking prevalence increases with the number of comorbid mental illnesses and that smokers with a mental disorder have lower success in quitting than smokers without mental illnesses [57] although there is solid evidence for the effectiveness of smoking cessation interventions for people even with severe mental disorders [58].…”
Section: Discussionmentioning
confidence: 99%
“…In psychosocial characteristics, low educational background were more likely to currently smoke (Morimoto, 2010) but those who had tried to quit (Clark, 1998) and smokers that already motivated (by themselves and support others) to quit are more likely to stop smoking and remain abstinent than smokers with no such motivation (Metse, 2016;Osler & Prescott, 1998). One of strategy which smokers received advice from their family or who perceive the health risks are more likely to reach abstinent (Hammar & Carlsson, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Those who had tried to stop smoking were about twice as likely to think to quit, attempt to quit and actually quit smoking (Clark, 1998). Participants (with mental illness) who not living with other smokers and perceiving their health provider to be supportive was more likely to have quit for a longer duration (Metse, 2016). Osler and Prescott, (1998) reported smokers motivated to quit smoking are more likely to stop smoking and remain abstinent than smokers with no such motivation (Osler M and Prescott, 1998).…”
Section: Individual Social and Psychological Characteristics Of Smokmentioning
confidence: 99%
“…The sociological perspective draws a strong association between low socioeconomic status and mental illness, with socioeconomic status being a risk factor for the uptake and continued use of tobacco [5] . Studies reporting both the prevalence of smoking and demographic and clinical characteristics of smokers with mental illness are scarce [32] . However, the few available studies revealed considerable controversy concerning sociodemographic determinants among this group.…”
Section: Discussionmentioning
confidence: 99%